2011
DOI: 10.1603/ec11145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature on the Life History Parameters and Population Growth Rates of Hyalopterus pruni (Hemiptera: Aphididae)

Abstract: The mealy plum aphid, Hyalopterus pruni (Geoffroy) (Hemiptera: Aphididae) is a pest of prune trees in California. The impact of aphids as pests is well characterized by their population growth rate, a parameter integrating their age-specific development, survivorship, and fecundity. These population parameters were measured at five constants temperatures on potted prune trees. Development rates increased with temperature up to an optimum. The relationship between development rate and temperature was described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Satar et al (2005) reported that developmental periods of immature stages of A. gossypii under laboratory conditions, ranged from 10.8 days at 15°C to 4.1 days at 30°C and 32.5°C. Adult longevity of Hyalopterus pruni (Geoffroy) decreased when the temperature increased (Latham and Mills 2011). Yang and Chi (2006) reported that mean developmental times of Bemisia argentifolii Bellows and Perring decreased with an increase in temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Satar et al (2005) reported that developmental periods of immature stages of A. gossypii under laboratory conditions, ranged from 10.8 days at 15°C to 4.1 days at 30°C and 32.5°C. Adult longevity of Hyalopterus pruni (Geoffroy) decreased when the temperature increased (Latham and Mills 2011). Yang and Chi (2006) reported that mean developmental times of Bemisia argentifolii Bellows and Perring decreased with an increase in temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The number of heat units accumulated during a specific period is an essential factor pest population dynamics (Latham & Mills, 2011). We used accumulated growing degree-days (GDD) above 9.475 °C, the average base developmental threshold temperature among 287 pest arthropods listed in the Insect Development Database (IDD) (NAPPFAST, 2015;Nietschke et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The CLIMEX model is a popular simulation software program [31,32] designed for conducting risk assessments for insect pests, weeds and diseases [33][34][35][36][37][38][39][40][41]. The program has the advantage, in comparison to other climate modeling softwares, that it includes a global meteorological database, which enables its Compare Locations module to be process-oriented.…”
Section: Introductionmentioning
confidence: 99%